The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/v12121390
|View full text |Cite
|
Sign up to set email alerts
|

Early Humoral Response Correlates with Disease Severity and Outcomes in COVID-19 Patients

Abstract: The Coronavirus Disease 2019 (COVID-19), caused by SARS-CoV-2, continues to spread globally with significantly high morbidity and mortality rates. Antigen-specific responses are of unquestionable value for clinical management of COVID-19 patients. Here, we investigated the kinetics of IgM, IgG against the spike (S) and nucleoproteins (N) proteins and their neutralizing capabilities in hospitalized COVID-19 patients with different disease presentations (i.e., mild, moderate or severe), need for intensive care u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 36 publications
6
38
1
Order By: Relevance
“…The only significant difference was the higher S1 IgM seroconversion rate observed in the deceased group that may suggest an early admission to hospital after infection. In other similar studies early antibody response to S1 IgA or IgM or difference in the magnitude of the immune response to SARS-CoV-2 infection was a predictor of disease severity or progression or outcome [34][35][36][37]. In this study, IgG antibody titers against NP at day 6 were significantly higher in the deceased group, as reported in other studies where an early response to NP during the first 15 days after disease onset was predictive of fatal outcome [34,36].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The only significant difference was the higher S1 IgM seroconversion rate observed in the deceased group that may suggest an early admission to hospital after infection. In other similar studies early antibody response to S1 IgA or IgM or difference in the magnitude of the immune response to SARS-CoV-2 infection was a predictor of disease severity or progression or outcome [34][35][36][37]. In this study, IgG antibody titers against NP at day 6 were significantly higher in the deceased group, as reported in other studies where an early response to NP during the first 15 days after disease onset was predictive of fatal outcome [34,36].…”
Section: Discussionsupporting
confidence: 85%
“…was observed for neutralizing antibodies between the recovered and deceased patients as, on the contrary, reported in other studies where neutralizing antibodies were significantly higher in patients who required ICU or died [36]. One possible explanation for the similar immune…”
Section: Plos Onementioning
confidence: 45%
“…To the best of our knowledge, this is one of the few studies showing that the levels of the adaptive humoral immune response to SARS-CoV-2 expressed as plasma concentrations of antibodies do not correlate with the presence of symptomatic disease. In contrast, others have suggested that factors such as high viral load, disease severity, and older age likely correlate with increased responsiveness of humoral immunity; however, these studies included hospitalized COVID-19 patients [11,[23][24][25]. Interestingly, in their most recent study, Sasisekharan et al [26] showed that anti-S1 and anti-RBD antibody levels could differentiate mild from moderate and severe cases, whereas anti-N antibodies could not clearly distinguish these categories, suggesting that associations between antibody titers and COVID-19 severity likely depend on the SARS-CoV-2-specific immunoassay used.…”
Section: Discussionmentioning
confidence: 99%
“…In the study from Röltgen K et al, antibody responses in acute illness were not related with patients` outcomes[2]. In contrast, Hashem AM et al reported significantly higher levels of anti-S1 and -N IgG and IgM antibodies in patients with fatal outcomes[11].Nonetheless, these studies include a mixture of mild, moderate and severe patients, with only a limited representation of critically ill patients. Previous work coming from our group evidence that the biological response of critically ill patients to SARS-CoV-2 infection differs from that of patients with milder forms of the disease[3].…”
mentioning
confidence: 96%
“…In turn, levels of anti-S antibodies correlated inversely with viral RNA load in plasma: (correlation coefficient, p): anti-SARS-CoV-2 S IgG / N1 (copies/mL) (-0.45, < 0.001); anti-SARS-CoV-2 S IgG / N2 (copies/mL) (-0.48, < 0.001); anti-SARS-CoV-2 S IgM / N1 (copies/mL) (-0.34, < 0.001); anti-SARS-CoV-2 S IgM / N2 (copies/mL) (-0.37, < 0.001) (Figure 3).DiscussionOur study demonstrates that those critically ill COVID-19 patients with absent or insufficient levels of specific IgM or IgG antibodies against the S protein of SARS-CoV-2 following ICU admission show an increased risk of mortality. Li et al found that the production of antibodies is delayed in severe COVID-19 patients as compared to non-severe ones[10], although the former seem to exhibit higher antibody concentrations than patients with milder forms of the disease[10] [11]. The impact of antibody levels on mortality risk in COVID-19 is controversial.…”
mentioning
confidence: 99%